The difference in mean arterial pressure induced by remimazolam compared to etomidate in the presence of fentanyl at tracheal intubation: A randomized controlled trial - Huang, Xiaofang; Cao, Huiyu; Zhang, Cuiwen; Lan, Hongmeng; Gong, Xiaofang; Li, Ruijie; Lin, Yan; Xu, Bing; Chen, Huihe; Guan, Xuehai (Frontiers in Pharmacology, 2023)
Background: Combined use of hypnotic and opioids during anesthesia inductions decreases blood pressure. Post-induction hypotension (PIHO) is the most common side effect of anesthesia induction. We aimed to compare the difference in mean arterial pressure (MAP) induced by remimazolam with that induced by etomidate in the presence of fentanyl at tracheal intubation. Methods: We assessed 138 adult patients with American Society of Anesthesiologists physical status I–II who underwent elective urological surgery. Patients were randomly allocated to receive either remimazolam or etomidate as alterative hypnotic in the presence of fentanyl during anesthesia induction. Comparable BIS values were achieved in both groups. The primary outcome was the difference in the MAP at tracheal intubation. The secondary outcomes included the characteristics of anesthesia, surgery, and adverse effects. Results: The MAP was higher in the etomidate group than in the remimazolam group at tracheal intubation (108 [22] mmHg vs. 83 [16] mmHg; mean difference, -26; 95% confidence interval [CI], -33 to -19; p < 0.0001). Heart rate was significantly higher in the etomidate group than in the remimazolam group at tracheal intubation. The patients` condition warranted the administration of ephedrine more frequently in the remimazolam group (22%) than in the etomidate group (5%) (p = 0.0042) during anesthesia induction. The remimazolam group had a lower incidence of hypertension (0% vs. 9%, p = 0.0133), myoclonus (0% vs. 47%, p < 0.001), and tachycardia (16% vs. 35%, p = 0.0148), and a higher incidence of PIHO (42% vs. 5%, p = 0.001) than the etomidate group during anesthesia induction. Conclusions: Remimazolam was associated with lower MAP and lower heart rate compared to etomidate in the presence of fentanyl at tracheal intubation. Patients in the remimazolam group had a higher incidence of PIHO, and their condition warranted the administration of ephedrine more frequently than in the etomidate group during anesthesia induction.